1974
DOI: 10.1210/endo-94-6-1628
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone and Testicular Cytochrome P-450: Decreased Testosterone Formation inSeveral Species and Changes in Hepatic Drug Metabolism1

Abstract: The daily administration of spironolactone caused a 40-90% decrease in the level of microsomal cytochrome P-450 in the testes of rat, guinea pig, rabbit, mouse and dog, but no reduction was detected in the amount of cytochrome b 5 . The loss of microsomal cytochrome P-450 was concomitant with a similar loss of both the microsomal heme associated with cytochrome P-450 and the activity of the microsomal 17a-hydroxylase. In contrast to its effects on the 17a-hydroxylase, spironolactone administration slightly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

1981
1981
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(29 citation statements)
references
References 12 publications
(13 reference statements)
3
25
0
1
Order By: Relevance
“…The absence of an effect of adrenalectomy or spironolactone treatment on the masses of the testis and accessory glands in this study is in agreement with published reports in the rat which show that adrenalectomy (Feek, Tuzi & Edwards, 1989) and spironolactone treatment (Menard, Stripp & Gilette, 1974) do not affect chronic circulating testosterone levels, or mass of the testes or seminal vesicles (Wong & Lee, 1982). Turner & Cesarini (1983), however, did report a small but significant effect on seminal vesicle (but not testis) weight.…”
Section: Concentration Of Electrolytes and Osmotic Pressure Of Blood supporting
confidence: 92%
“…The absence of an effect of adrenalectomy or spironolactone treatment on the masses of the testis and accessory glands in this study is in agreement with published reports in the rat which show that adrenalectomy (Feek, Tuzi & Edwards, 1989) and spironolactone treatment (Menard, Stripp & Gilette, 1974) do not affect chronic circulating testosterone levels, or mass of the testes or seminal vesicles (Wong & Lee, 1982). Turner & Cesarini (1983), however, did report a small but significant effect on seminal vesicle (but not testis) weight.…”
Section: Concentration Of Electrolytes and Osmotic Pressure Of Blood supporting
confidence: 92%
“…In the present study, the total protein content decrease in the testes of albino rats may be due to the side effects of thiazide drug compound. In the present study it has also been reported by Menard (1974). It is likely that the lipoprotein and protein contents decreases by the adverse effect of thiazide and is mainly characterized by degradation of microsomal cytochrome p-450; while Fanestil (1997) reported in the kidney the metabolic influence of drug hydrochlorothiazide.…”
Section: Discussionsupporting
confidence: 79%
“…There have been many reports addressing the mechanism of this action. Menard et al (22) demonstrated, in several species, that spironolactone treatment decreases the microsomal cytochrome P 450 content of the testes and reduces the activity of 17-hydroxylase, an enzyme necessary for testosterone synthesis. In women treated with spironolactone to reduce hirsutism, this drug has been shown to increase testosterone clearance (23) and decrease genital skin fibroblast steroid 5α reductase (24).…”
Section: Discussionmentioning
confidence: 99%
“…Different explanations have been offered for the hormonal changes induced by these drugs, and spironolactone in particular. These include reduction in testosterone synthesis (22,23), increase in testosterone clearance (23), reduction of 5α-reductase activity (24), and interference with AR activity (25). To date, no report has defined the effects of these drugs on the sex hormone receptor state of the liver.…”
mentioning
confidence: 99%